Non-aqueous lithium ion battery electrolyte and application thereof

By using fluorinated benzene-containing additives in the lithium-ion battery electrolyte, the components of the negative electrode SEI film are regulated, and the problems of prolonged infiltration time and poor circulation performance of the electrolyte on high-pressure electrode sheets are solved, and higher infiltration ability and electrochemical performance are achieved.

CN119518094AInactive Publication Date: 2025-02-25ZHEJIANG YONGTAI NEW ENERGY MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411607954.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to regulate the solid electrolyte layer at the active substance-electrolyte interface while shortening the infiltration time of the electrolyte on the high-pressure electrode sheet, resulting in a high internal resistance of the battery and poor circulation performance.

Method used

Using a non-aqueous lithium-ion battery electrolyte containing lithium salts, organic solvents and fluorinated benzene-containing high-impregnation additive, the components of the negative electrode SEI film are regulated to form more LiF components that are favorable to ion transport.

Benefits of technology

It significantly improves the battery's wetting ability on high-pressure pole sheets, improves the stability of room temperature and high-temperature circulation, reduces high-temperature storage gas production, extends storage life, and improves capacity retention rate at ultra-low ambient temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a non-aqueous lithium ion battery electrolyte and application thereof. The lithium ion battery electrolyte comprises the following components: a lithium salt, an organic solvent and an additive, the additive comprises one of a silane additive, a vinyl ester additive, a sulfur-containing additive and a compound shown as a formula (I). Through the combined use of one or more compounds in the formula (I), the infiltration time of the electrolyte on a high-compaction pole piece can be shortened, the components of the active substance-electrolyte interface solid electrolyte layer can be regulated and controlled, the excellent cycle performance of the battery is ensured, and the high-temperature storage performance and the like of the battery cannot be degraded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a formula of a non-aqueous lithium ion battery electrolyte and application thereof. Background Art

[0002] Lithium iron phosphate batteries have shown great application potential and market prospects in the fields of energy storage and power applications due to their advantages in safety, cost-effectiveness, environmental protection and technical adaptability. As the market's requirements for the energy density of lithium iron phosphate batteries for energy storage and power increase, the compaction density and coating thickness of the battery gradually increase, and higher requirements are also placed on the wettability of the electrolyte.

[0003] As one of the common positive electrode materials, lithium iron phosphate (LiFePO4) has a series of advantages such as high safety performance, long cycle life, wide source of raw materials, and low price. With the continuous pursuit of battery life and the development of lithium-ion battery manufacturing technology, one of the important development goals of lithium iron phosphate batteries is to improve energy density.

[0004] The theoretical capacity density of lithium iron phosphate materials is currently close to the limit, and there is little room for modifying lithium iron phosphate itself by coating and other methods to increase capacity. The compaction density is defined as the ratio of the coating surface density of the pole piece material to the thickness of the pole piece surface material after compaction. The greater the compaction density, the more active materials a battery of the same specification contains, which means a higher energy density. Therefore, one of the common technical means at present is to increase the energy density of lithium iron phosphate single cells by significantly increasing the compaction density of the lithium iron phosphate positive pole piece.

[0005] However, there are still some problems that need to be solved when high compaction density electrodes are put into actual use. High compaction density means that the space between the particles of active materials loaded on the positive / negative current collectors is reduced, which increases the difficulty of the electrolyte penetrating the electrode. If the electrolyte does not penetrate the positive / negative active materials sufficiently, the internal resistance of the battery will be high. In severe cases, lithium precipitation will occur, leading to an internal short circuit. Under the condition of the same injection volume, it is necessary to ensure that the electrolyte completely penetrates the high-density electrode by extending the time / increasing the temperature / increasing the vacuum degree, which will cause certain losses to the production line efficiency and even economic benefits. Designing a new type of electrolyte that takes into account both efficient wettability and excellent cycle performance is currently a research focus of many companies in the industry.

[0006] For example, Chinese patent CN112110953A discloses a phosphate compound, a synthesis method of the phosphate compound and its non-aqueous electrolyte. The main means of inhibiting side reactions on the electrode surface include coating the electrode active material and adding an effective film-forming additive to the electrolyte to form a passivation film of sufficient thickness and density on the electrode surface. The purpose of these two means is undoubtedly to prevent the electrolyte from contacting the electrode surface and thus gaining or losing electrons, and at the same time prevent the electrode surface from being corroded by the decomposition byproducts of the electrolyte. The beneficial effects of the phosphate compound of the invention are: high thermal stability and easy storage, strong compatibility with other components of the electrolyte and other components inside the battery, moderate viscosity, high dielectric constant, solubility of lithium salts, certain wetting ability, and both flame retardant and positive and negative electrode surface film forming functions. However, the preparation process of the invention is complicated.

[0007] For example, patent CN112010894B discloses a sulfur phosphate compound, a synthesis method and a non-aqueous electrolyte. When the above compound is applied to a battery with a non-aqueous electrolyte, the electrode / electrolyte interface of the lithium-ion battery is effectively improved even when the battery is under high voltage, thereby stabilizing the electrode surface film, reducing side reactions, improving the stability of the battery at high temperature and high voltage, and improving the battery cycle stability; at the same time, the self-extinguishing time of the non-aqueous electrolyte after combustion is shortened, the flame retardant ability is improved, and the safety performance of the battery is improved. However, its ability to wet the positive and negative pole pieces needs to be studied.

[0008] Therefore, there is an urgent need to provide an electrolyte that can shorten the electrolyte infiltration time for high-pressure solid electrodes and regulate the composition of the solid electrolyte layer at the active material-electrolyte interface to improve the electrochemical properties of the battery. Summary of the invention

[0009] Based on the problems existing in the prior art, the present invention provides a non-aqueous lithium-ion battery electrolyte, which can improve its wettability to the electrode sheet while better regulating the components of the positive and negative solid electrolyte layers, thereby improving the long-term cycle performance and high-temperature storage performance of the lithium-ion battery.

[0010] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0011] In one aspect, the present invention provides a non-aqueous lithium ion battery electrolyte, comprising the following components: a lithium salt, an organic solvent and an additive;

[0012] The additive is selected from silane additives, vinyl ester additives, sulfur-containing additives and benzene-containing additives, and the benzene-containing additive is one or more of the compounds represented by formula (I);

[0013]

[0014] In the formula, R1-R6 are independently H, halogen atoms, C 1-6 Saturated alkyl or C 1-6 The haloalkyl group is selected from one or more of a fluoroalkyl group, a brominated alkyl group or a chloroalkyl group.

[0015] Preferably, the halogen atom is one of a fluorine atom, a chlorine atom and a bromine atom;

[0016] More preferably, the halogen atom is a fluorine atom;

[0017] Preferably, the C 1-6 The saturated alkyl group is a chain alkyl group; the alkyl group is one of methyl, ethyl, n-propyl, n-butyl, n-pentyl and n-hexyl;

[0018] Preferably, the C 1-6 The fluoroalkyl group is an alkyl group in which 1 to 3 carbon atoms are substituted by fluorine; the fluoroalkyl group is one of monofluoromethyl, difluoromethyl, trifluoromethyl, monofluoroethyl, difluoroethyl, trifluoroethyl, monofluoro-n-propyl, difluoro-n-propyl, difluoro-n-propyl, monofluoro-n-pentyl, difluoro-n-pentyl, trifluoro-n-pentyl, monofluoro-n-butyl, difluoro-n-butyl, trifluoro-n-butyl, tetrafluoro-n-butyl, monofluoro-n-hexyl, difluoro-n-hexyl and trifluoro-n-hexyl.

[0019] Preferably, the benzene-containing additive is selected from any one of the following structural formulas:

[0020]

[0021] Preferably, the added amount of the compound represented by formula (I) is 1-4% by mass of the electrolyte.

[0022] Preferably, the silane additive is tris(trimethylsilyl)phosphate (TMSP); the vinyl ester additive is vinylene carbonate (VC) and fluoroethylene carbonate (FEC); the sulfur-containing additive is diethylene sulfate (DTD);

[0023] Preferably, the mass ratio of vinylene carbonate (VC) to fluoroethylene carbonate (FEC) is 4:1.

[0024] Preferably, the mass percentage of the silane additive in the electrolyte is 0.2%-5%; the mass percentage of the vinyl ester additive in the electrolyte is 0.2%-5%; the mass percentage of the sulfur-containing additive in the electrolyte is 0.2%-5%.

[0025] More preferably, the mass percentage of the silane additive in the electrolyte is 0.4%; the mass percentage of the vinyl ester additive in the electrolyte is 3%; and the mass percentage of the sulfur-containing additive in the electrolyte is 0.7%.

[0026] Preferably, the lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethyl)sulfonylimide (LiTFSI), lithium difluorooxalatoborate (LiODFB), and lithium tetrafluoroborate (LiBF4); preferably lithium hexafluorophosphate (LiPF6);

[0027] Preferably, the concentration of the lithium salt is 1M.

[0028] Preferably, the organic solvent is selected from one or more of chain carbonates, cyclic carbonates, carboxylates, chain fluorinated carbonates, cyclic fluorinated carbonates, fluorinated carboxylates, and fluorinated ethers.

[0029] Preferably, the chain carbonates mainly include one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate;

[0030] Preferably, the cyclic carbonates mainly include one or more of ethylene carbonate, vinylene carbonate and propylene carbonate;

[0031] Preferably, the carboxylic acid esters mainly include one or more of ethyl acetate, ethyl propionate, methyl propionate, propyl propionate, methyl butyrate, and ethyl butyrate;

[0032] Preferably, the chain fluorinated carbonate mainly comprises one or more of methyl trifluoroethyl carbonate, ethyl trifluoroethyl carbonate, and bis(trifluoroethyl) carbonate;

[0033] Preferably, the fluorinated cyclic carbonate mainly comprises one or more of fluorinated ethylene carbonate, trifluoromethyl ethylene carbonate, bis(trifluoromethyl) carbonate, and trifluoroethyl ethylene carbonate.

[0034] As some preferred embodiments, the organic solvent is ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC);

[0035] Preferably, the volume ratio of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) is: 25-35:15-25:45-55;

[0036] More preferably, the volume ratio of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) is 30:20:50.

[0037] The present invention also provides the use of the non-aqueous lithium ion battery electrolyte in the preparation of lithium ion batteries.

[0038] Preferably, the preparation method of the lithium ion battery comprises the following steps: injecting the above-mentioned non-aqueous lithium ion battery electrolyte into a soft-pack lithium ion battery that has been dried at 80°C for 24 hours, and performing processes such as placing at 45°C, high-temperature fixture formation and secondary sealing to obtain the lithium ion battery.

[0039] Preferably, the lithium-ion battery further comprises a positive electrode sheet, a negative electrode sheet, a separator and an outer package, wherein the positive electrode sheet comprises a positive electrode current collector, a positive electrode active material, a conductive agent and a binder;

[0040] Preferably, the positive electrode sheet comprises a metal copper current collector, a positive electrode active material, a conductive agent and a binder;

[0041] Preferably, the positive electrode active material is LiFePO4;

[0042] Preferably, the compaction density of the positive electrode sheet is 2.55 gcm -3 ;

[0043] Preferably, the negative electrode plate comprises a metal aluminum current collector, a negative electrode active material, a conductive agent, a thickener and a binder;

[0044] Preferably, the negative electrode active material is a composite of one or more of artificial graphite, natural graphite, composite graphite, graphene, carbon nanotubes, nano silicon balls, silicon-carbon composite materials, and silicon-oxygen composite materials;

[0045] Preferably, the compaction density of the negative electrode sheet is 1.6 gcm -3 ;

[0046] Preferably, the diaphragm is a high molecular weight polyolefin diaphragm.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] In the electrolyte disclosed in the present invention, by using the high wetting additive containing polyfluorinated benzene described in formula (I), the F element is introduced to shorten the time for the electrolyte to infiltrate the high-pressure electrode, and at the same time, the components of the negative electrode SEI film are optimized to form more LiF components that are beneficial to ion transmission, thereby meeting the room temperature long cycle of the lithium iron phosphate full battery and improving the high-temperature cycle stability and high-temperature storage performance. DETAILED DESCRIPTION

[0049] The technical scheme of the present invention is clearly and completely described below with specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The materials, reagents, etc. used, if not otherwise specified, are reagents and materials available from commercial sources.

[0050] Unless otherwise indicated, the following terms have the following meanings. Any undefined term has its generally accepted meaning in the field. "Percentage" as described in the text refers to "mass percentage".

[0051] The compounds used below are compounds represented by formula (I) of the present invention, and their structural formulas are:

[0052]

[0053] The main components and proportions of each comparative example and embodiment are shown in Table 1:

[0054] Table 1 Components and contents of electrolytes in comparative examples and embodiments

[0055]

[0056]

[0057]

[0058] The above-mentioned embodiments and comparative examples were prepared into lithium-ion batteries according to the following method: the above-mentioned non-aqueous lithium-ion battery electrolyte was injected into a soft-pack lithium-ion battery that had been dried at 80 degrees Celsius for 24 hours, and the lithium-ion battery was obtained after being placed at 45 degrees Celsius, formed in a high-temperature fixture, and sealed twice.

[0059] Effect Experiment

[0060] 1. Test of initial battery performance

[0061] The lithium-ion batteries prepared in the above-mentioned embodiments and comparative examples were subjected to charging and discharging tests, and the current and voltage changes during the charging and discharging process were recorded. The fractional capacity, the first cycle coulomb efficiency and the first cycle coulomb efficiency can be directly read by the battery test cabinet. The experiment was repeated three times and the average value was calculated. The results are shown in Table 2.

[0062] Table 2 Test results of initial performance of batteries prepared in various embodiments and comparative examples

[0063]

[0064]

[0065] 2. Lithium-ion battery performance test

[0066] Electrolyte wettability test:

[0067] Maintaining room temperature (25°C), place the prepared high-pressure solid electrode (positive lithium iron phosphate / negative graphite) in a dry glass dish with a lid. Use a pipette to absorb a certain amount of the electrolyte of the embodiment and the comparative example, and drop it on the surface of the high-pressure solid electrode. Evaluate the electrolyte wetting performance by recording the time when the electrolyte disappears. The shorter the time when the electrolyte disappears on the surface of the electrode, the better the electrolyte wetting performance. The viscosity is tested by an Ubbelohde viscometer to obtain the corresponding data.

[0068] Normal temperature cycle performance:

[0069] The prepared lithium-ion battery was charged to 3.65V at 1C current at room temperature (25°C), and then charged at 3.65V at a constant voltage until the current reached 0.05C; then discharged to 2.5V at 1C constant current, and recorded as one cycle. The discharge capacity of the first cycle was recorded as DC1. After 500 cycles of charge and discharge, the discharge capacity of the 500th cycle was recorded as DC 500 , the capacity retention rate after the 500th cycle is calculated as follows:

[0070]

[0071] 45℃ high temperature cycle performance:

[0072] The prepared lithium-ion battery was charged to 3.65V at a constant current of 1C at high temperature (45°C), and then charged at a constant voltage of 3.65V until the current reached 0.05C; then discharged to 2.5V at a constant current of 1C, and recorded as one cycle. The discharge capacity of the first cycle was recorded as DC1; after 500 cycles of charge and discharge, the discharge capacity of the 500th cycle was recorded as DC 500 , the capacity retention rate after the 500th cycle is calculated as follows:

[0073]

[0074] 60℃ Storage Performance:

[0075] At room temperature (25°C), the lithium-ion battery is discharged and charged at 1C / 1C, and the average thickness of the battery is measured as d1, and the charging capacity is C1; the lithium-ion battery is placed in a 60°C high-temperature oven for 14 days; after 14 days, the battery is taken out and discharged at 1C to 2.5V, and the discharge capacity is recorded as C2; the thickness is measured as d2, and the thickness change rate and capacity retention rate after 14 days of storage at 60°C are calculated according to the following two formulas:

[0076]

[0077] -20℃ discharge performance:

[0078] At room temperature (25°C), the lithium-ion battery is first charged at 1C, and the battery capacity is recorded as C3; then, the battery is placed in a low-temperature box, the temperature is controlled at -20°C, and discharged at 1C to 2.5V, and the discharge capacity is recorded as C4; the -20°C discharge performance is calculated as follows:

[0079]

[0080] The battery test results of Comparative Example 1 and Examples 1-20 are shown in Table 3 and Table 4 below.

[0081] Table 3 Battery performance test results obtained from the preparation of each comparative example and embodiment (1)

[0082]

[0083]

[0084] Table 4 Battery performance test results obtained from the preparation of each comparative example and embodiment (2)

[0085]

[0086]

[0087] The non-aqueous lithium ion electrolyte containing fluorobenzene additives disclosed in the present invention provides lithium ion batteries with better electrochemical performance on the basis of satisfying the primary goal of improving the wetting ability to high-voltage solid electrodes.

[0088] According to the test results, the following conclusions can be drawn:

[0089] The results of Comparative Example 1 and Examples 1-4 show that the introduction of the fluorobenzene additives of the present invention into the electrolyte significantly reduces the wetting time and viscosity because the solubility of fluorobenzene in the electrolyte salt is extremely low, and it basically does not participate in the coordination with the Li ion, and plays the role of a diluent, and the F group can improve the wetting effect; it is worth noting that the wetting effect does not increase with the increase in the number of fluorine substituents on the benzene ring;

[0090] The results of Comparative Example 1 and Examples 2-20 show that when one fluorobenzene additive reaches 3% and the other fluorobenzene additive is 1%, the wetting effect is mainly controlled by the high content, i.e., 3% of the fluorobenzene additive. The combination of different types of fluorobenzene additives and the content of the additives need to be further adjusted;

[0091] The results of Comparative Example 1 and Examples 1-4 show that the number of fluorine substituents has a different trend in the effect on battery performance. Example 2 has the best room temperature cycle performance, and Example 4 has the best 45 degrees Celsius high temperature cycle performance. The results of Examples 8, 12, 16, and 20 show that adding compound 8 reduces battery performance.

[0092] The results of Comparative Example 1 and Examples 1-4 show that fluorobenzene additives can inhibit the growth of DCR of the battery during room temperature cycling; Comparative Example 1 is compared with all the examples in which fluorobenzene is added, indicating that all combinations of fluorobenzene additives can improve the discharge performance of lithium-ion batteries in an environment of -20°C, and the discharge performance is not controlled by the number of fluorinated groups.

[0093] The results of Comparative Example 1 and Examples 1-4 show that fluorobenzene additives improve the normal temperature and high temperature long cycle and high temperature storage performance of the battery. Specifically, compared with Comparative Example 1, 4% fluorobenzene additives increased the capacity retention rate of 500 weeks of normal temperature and high temperature long cycle; effectively reduced the gas blistering during high temperature storage, and improved the capacity retention rate after 14 days of high temperature storage;

[0094] Example 2, Example 5, Example 9, Example 13 and Example 17 illustrate that the use of a compound containing two substituents on the benzene ring as an additive can both reduce the wetting time and improve the battery performance.

[0095] From the above conclusions, it can be concluded that the application of the non-aqueous electrolyte provided by the present application to lithium-ion batteries can improve the comprehensive performance of high-pressure positive and negative lithium-ion batteries. Specifically, it can improve the wetting ability of high-pressure electrode sheets, construct a fluorine-rich electrolyte-electrode interface, and improve the room temperature and high temperature cycle stability, reduce the gas production of the battery during high-temperature storage, and thus extend the storage life; at ultra-low ambient temperature (-20°C), it can improve the capacity retention rate by promoting lithium ion dynamics.

Claims

1. A non-aqueous lithium ion battery electrolyte comprising the following components: a lithium salt, an organic solvent and an additive; The additive is selected from silane additives, vinyl ester additives, sulfur-containing additives and benzene-containing additives, and the benzene-containing additive is one or more of the compounds represented by formula (I); In the formula, R1-R6 are independently H, halogen atoms, C 1-6 Saturated alkyl or C 1-6 The haloalkyl group is selected from one or more of a fluoroalkyl group, a brominated alkyl group or a chloroalkyl group.

2. The non-aqueous lithium ion battery electrolyte according to claim 1, characterized in that: The silane additive is tris(trimethylsilane) phosphate; the vinyl ester additive is vinylene carbonate and fluoroethylene carbonate; the sulfur-containing additive is vinyl sulfate; the benzene-containing additive is selected from any one of the following structural formulas:

3. The non-aqueous lithium ion battery electrolyte according to claim 1, characterized in that: Calculated by mass percentage of the non-aqueous lithium-ion battery electrolyte, the silane additive accounts for 0.2%-5%; the vinyl ester additive accounts for 0.2%-5%; the sulfur-containing additive accounts for 0.2%-5%; and the benzene-containing additive accounts for 1%-4%.

4. The non-aqueous lithium ion battery electrolyte according to claim 1, characterized in that: The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonylimide, lithium difluorooxalatoborate, and lithium tetrafluoroborate.

5. The non-aqueous lithium ion battery electrolyte according to claim 4, characterized in that: The lithium salt is lithium hexafluorophosphate with a concentration of 1M.

6. The non-aqueous lithium ion battery electrolyte according to claim 1, characterized in that: The organic solvent is selected from one or more of chain carbonate organic solvents, cyclic carbonate organic solvents, carboxylate organic solvents, chain fluorinated carbonate organic solvents, cyclic fluorinated carbonate organic solvents, fluorinated carboxylate organic solvents and fluorinated ether organic solvents.

7. The non-aqueous lithium ion battery electrolyte according to claim 6, characterized in that: The cyclic carbonate organic solvent and the chain carbonate organic solvent are ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate respectively, and the volume ratio of the three is: 25-35:15-25:45-55.

8. Use of the non-aqueous lithium ion battery electrolyte according to any one of claims 1 to 7 in the preparation of lithium ion batteries.

9. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and an outer package and the non-aqueous lithium ion battery electrolyte according to any one of claims 1 to 7.

10. The lithium ion battery according to claim 9, characterized in that: The preparation method of the lithium ion battery comprises the following steps: injecting the non-aqueous lithium ion battery electrolyte described in any one of claims 1 to 7 into a soft-pack lithium ion battery that has been dried at 80° C. for 24 hours, and performing processes such as placing at 45° C., high-temperature fixture formation, and secondary sealing to obtain the lithium ion battery.

Citation Information

Patent Citations

  • Phosphate compound and synthetic method thereof, and non-aqueous electrolyte

    CN112110953A

  • Functional additive for lithium ion battery electrolyte, electrolyte and lithium ion battery

    CN108539267A

  • Non-aqueous electrolyte and lithium ion battery

    CN112467202A

  • Lithium ion battery electrolyte and lithium ion battery

    CN117096442A

  • Electrolyte and preparation method and application thereof

    CN117558980A